RAILWAY CONSTRUCTION - Boymuratov Norbek Khurramovich; Ergashev Jamshid Toshtemirovich (Bright Mind Publishing, 2026)
This scientific article presents a DSc-level comprehensive analysis of railway construction as an integrated engineering process encompassing geotechnical preparation, substructure stabilization, superstructure installation, and long-term structural performance under modern operational demands. The research investigates soil–structure interaction mechanisms, ballast behavior, track stiffness harmonization, dynamic load propagation, and the influence of high axle loads and increasing train speeds on track durability. Particular attention is devoted to subgrade preparation, embankment stability, drainage systems, sleeper–ballast interaction, and stress redistribution within rail–track systems. Analytical modeling based on elastic foundation theory, dynamic amplification principles, and structural mechanics is applied to evaluate deformation patterns and service life thresholds. The findings establish a system-oriented reconstruction and modernization framework aimed at improving reliability, safety, and sustainability of railway infrastructure in the context of increasing traffic intensity and climate variability.
Keywords: Railway construction, track substructure, ballast behavior, dynamic load, elastic foundation, soil–structure interaction, infrastructure modernization, structural reliability.